LEARNING-ORIENTED ASSESSMENT TO ASSESS QUR'AN READING AND WRITING SKILLS: COMPREHENSIVELY AND CONTINUOUSLY - Lubis, Ardiansyah; Kusaeri, Kusaeri; Suparto, Suparto; Zaitun, Zaitun; Yuliharti, Yuliharti; Ginda, Ginda; Indra, Adam Malik (Universitas Labuhanbatu, 2025)
Purpose – This study aims to examine the Learning-Oriented Assessment (LOA) model and its implementation to comprehensively and sustainably assess Qur'an reading and writing skills, as well as to identify the factors that support or inhibit its implementation.Methodology – This study employed the systematic literature review (SLR) method to analyze 24 articles published between 2020 and 2025 that focus on learning-oriented assessments for evaluating comprehensive and sustainable Al-Qur'an reading and writing skills. A thematic analysis was conducted to identify the main themes that emerged from the articles.Findings – The findings show that LOA is a participatory, reflective and process-oriented assessment approach, with five main models, namely 2D-LoA, EAT Framework, CSA-CT, Ecological LOA and ELOA, and five implementation patterns: self-assessment and peer-assessment, formative feedback and feedforward, authentic tasks and reflective projects, digital technology integration and collaboration in determining assessment criteria. Supporting factors include teacher competence and reflective orientation, active student participation, authentic and process-oriented task design, technological support, and an inclusive classroom climate and assessment culture. Meanwhile, barriers identified include the dominance of summative assessment and test culture, low assessment literacy among teachers, time constraints and administrative burdens, student resistance to new assessment practices, limited infrastructure and access to technology, and lack of institutional and policy support.Contribution–This research contributes significantly to the development of an assessment model that goes beyond traditional summative evaluation, with an approach that prioritizes continuous feedback and active student engagement in the learning process